2008
DOI: 10.1002/anie.200705463
|View full text |Cite
|
Sign up to set email alerts
|

A Straightforward Route to Helically Chiral N‐Heteroaromatic Compounds: Practical Synthesis of Racemic 1,14‐Diaza[5]helicene and Optically Pure 1‐ and 2‐Aza[6]helicenes

Abstract: Helicenes have attracted attention as unique inherently chiral three-dimensional aromatic compounds for several decades. Despite significant recent progress in the synthesis and applications of carbohelicenes and thiaheterohelicenes, [1] the potential of the aza analogues with a pyridine unit (pyridohelicenes) have not been explored. [2,3] There are only scattered examples of the preparation of pyridohelicenes, [4] but with no general synthetic methodology, since the photochemical approach can fail with pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(71 citation statements)
references
References 30 publications
(22 reference statements)
2
69
0
Order By: Relevance
“…The preparation of helicenes 81 and 82 [60] involves the [2 + 2 + 2] cyclotrimerization of regioisomeric aromatic triynes 83 and 84 using a Co(I)-catalyzed reaction as the major synthetic step to obtain tetrahydrohelicenes 85 (82%) and 86 (89%), respectively (Scheme 13). Finally, the MnO 2 -based oxidation resulted in rac aza [6]helicene 81 (65%) and 82 (53%).…”
Section: Scheme 11mentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of helicenes 81 and 82 [60] involves the [2 + 2 + 2] cyclotrimerization of regioisomeric aromatic triynes 83 and 84 using a Co(I)-catalyzed reaction as the major synthetic step to obtain tetrahydrohelicenes 85 (82%) and 86 (89%), respectively (Scheme 13). Finally, the MnO 2 -based oxidation resulted in rac aza [6]helicene 81 (65%) and 82 (53%).…”
Section: Scheme 11mentioning
confidence: 99%
“…Finally, the MnO2-based oxidation resulted in rac aza [6]helicene 81 (65%) and 82 (53%). The optical resolution of helicene 81 was carried out through the diastereomeric salt formation with optically pure (+)-O,O′-dibenzoyl-D-tartaric acid, whereas enantiopure 82 was obtained by separation of the corresponding racemic mixture with chiral HPLC (Scheme 13) [60].…”
Section: Scheme 11mentioning
confidence: 99%
“…31 We believe this is the first example of axial to helical chiral relay using such cycloisomerization chemistry. The apparent loss of stereochemical information is likely within error of the measurement, since product racemization, 14 would not be significant under these conditions (see Supporting Information). The high fidelity transfer of stereochemical information from biaryl 6 to helicene 4 opens up the possibility of an enantioselective synthesis of azahelicenes using this strategy in the future, via enantioselective synthesis of biaryl 6.…”
Section: Bromoalkynesmentioning
confidence: 99%
“…1 These chiral aromatics have promise to have wide-ranging impact, with preliminary studies already reported in the fields of catalysis, 2-7 non-linear optics, 8 electrooptical switches 9 and molecular recognition 10-13 amongst others. Azahelicenes (such as 4) have been a particularly exciting target class of helicenes recently for chemical synthesis, [1][2][3]14 exhibiting fascinating coordination chemistry, [13][14][15][16] self-assembly potential 17 and interesting photophysics. 18 We have recently demonstrated the high potential of this class in materials science, using enantiopure dopant quantities of 1-aza [6]helicene (4) to induce circularly polarized (CP) electroluminescence from an achiral light emitting polymer, 19 and fabricating organic phototransistors based on 4 that can reversibly detect CP light.…”
mentioning
confidence: 99%
See 1 more Smart Citation